Study of the structure of amorphous carbon films modified with silicon oxide - Ryaguzov, A.P.; Kudabayeva, M.A.; Nemkayeva, R.R.; Guseinov, N.R; Myrzabekova, M.M. (Publ. House of the KarSU named after acad. E.A.Buketov, 2019)
This paper considers amorphous carbon films modified with silicon oxide (а-C1-x:(SiO)х),obtained by the method of magnetron ion-plasma co-sputtering of a combined target in an argon atmosphere. The topography and phase contrast of the film surface were studied by atomic force microscopy. The local structure was studied by Raman spectroscopy. It is shown that an increase in the concentration of silicon leads to an increase in the intensity of photoluminescence. The shift of the G peak to the lowfrequency region in a-C1-x:(SiO)x films indicates an increase in the sp3 hybridization of carbon bonds.
Keywords: silicon containing amorphous carbon films; atomic force microscopy; Raman spectroscopy; photoluminescence; bond hybridization